Holding Our Learning and Unlearning - Amara Lynch (Adult Education Research Conference, 2025)
This research explores the interplay between personal and societal transformation by studying a learning community of parents of White sons seeking to parent in ways that disrupt patterns of oppression.
Keywords: Adult education; Social justice parenting; White male privilege; Action research